1988
DOI: 10.1136/bmj.296.6626.885
|View full text |Cite
|
Sign up to set email alerts
|

Fetal intracardiac transfusions in patients with severe rhesus isoimmunisation

Abstract: Six patients with pregnancies of 19-31 weeks' duration showing evidence of erythroblastosis fetalis were treated with 25 fetal intracardiac blood transfusions. Complications related to the procedure occurred on five occasions in three patients. In two of the six patients the fetus died, but it was unlikely that death was related to the intracardiac transfusions. Fetal intracardiac blood transfusion may result in potentially severe complications but offers an alternative when transfusion cannot be performed int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 6 publications
0
41
0
3
Order By: Relevance
“…The baseline characteristics of these women are summarized in Table 1. Ten women were noted to have had at least one previous stillbirth as a result of alloimmunization at a median gestational age of 24 weeks (range, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Of this cohort, 26 (87%) were associated with anti-D, four (13%) with anti-Kell and 12 had more than one antibody type involved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The baseline characteristics of these women are summarized in Table 1. Ten women were noted to have had at least one previous stillbirth as a result of alloimmunization at a median gestational age of 24 weeks (range, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Of this cohort, 26 (87%) were associated with anti-D, four (13%) with anti-Kell and 12 had more than one antibody type involved.…”
Section: Resultsmentioning
confidence: 99%
“…Objective To determine perinatal outcome in pregnancies with early severe red blood cell (RBC) IUT was 20.4 (range,[16][17][18][19][20][21][22] weeks, and between one and nine transfusions were needed during pregnancy. Transfusion was via the intrahepatic vein (IHV) (n = 19), umbilical vein (n = 6) or umbilical artery (n = 2), or was intracardiac (n = 2) or intraperitoneal (n = 1).…”
Section: Introductionmentioning
confidence: 99%
“…In three patients, increased amount of fluid in the pericardial space could be observed immediately after the procedure, suggesting haemopericardium. In one of these cases it was possible to aspirate the blood (previously described in detail [13]) while the other two exspired soon after the transfusion. Post-mortem examinations were performed revealing car- The clots in the pericardial space consisted of sero-negative blood which, at least, in one of the patients who had received a first transfusion, indicated that the transfusion had been wrongly administered into the pericardial space.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed description of the technique of intracardiac transfusion has recently been published [13]. After insertion of the needle, 3.0-4 ml of fetal blood was drawn for analyis of haematological indices (COULTER Counter 5 plus 3), acid-base balance (Coning 178 pH blood gas analyzer) and No.…”
Section: Methodsmentioning
confidence: 99%
“…Com uma taxa de sucesso maior que 90%, baixo índice de complicações, principalmente bradicardia fetal (menor que na funiculocentese) e sangramento intraperitoneal que acaba sendo reabsorvido 46 . A transfusão fetal intracardíaca, com uma taxa de complicações de 20%, fica reservada para casos em que o acesso a outra via não foi possível, sendo também descrita na ressuscitação de fetos exanguinados por hemorragia pós-funiculocentese 47 . O hematócrito alvo após a conclusão da TIU varia amplamente entre os diversos serviços, entre 30 e 60% 48 , sendo mais frequentemente adotado entre 40 e 50% 16 ou hemoglobina fetal entre 14 e 18 g/dL 49 .…”
Section: Seguimento E Terapêuticaunclassified